Peningkatan Hasil Belajar Matematika Melalui Metode Resitasi dan Kerja Kelompok - Desnilam K. Harefa (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The teacher as the sole learning resource in the classroom makes students passive in accepting learning. The purpose of this study was to determine the learning outcomes of mathematics in multiplication and division counting operations in class III-B SD Negeri 070986 Ononamolo I Lot, South Gunungsitoli District, could be increased, by using the recitation method and group work methods. This research was carried out in class III-B of SD Negeri 070986 Ononamolo I Lot, South Gunungsitoli District, 2019/2020 academic year, and its implementation was in the first semester. In the first cycle, the application of the Recitation learning model and group work methods on the material Operation counting multiplication and division has not reached the target which are expected. This is based on 38.7% of students' mastery learning which has not yet reached the target. In the second cycle, learning through the application of the Recitation learning model and group work methods has increased. This is based on 90.3% student learning completeness, which means that it has reached the target. Keywords: counting operations; group work; recitation  Abstrak: Guru sebagai sumber belajajr tunggal di dalam kelas membuat siswa menjadi pasif dalam menerima pembelajaran. Tujuan penelitian ini adalah untuk mengetahui hasil belajar Matematika Pada Operasi hitung perkalian dan pembagian di  kelas III-B SD Negeri 070986 Ononamolo I Lot Kecamatan Gunungsitoli Selatan dapat meningkat, dengan menggunakan metode resitasi dan metode kerja kelompok. Penelitian ini dilaksanakan di kelas III-B SD Negeri 070986 Ononamolo I Lot Kecamatan Gunungsitoli Selatan Tahun Pelajaran 2019/2020, dan pelaksanaannya pada semester I. Pada siklus I penerapan model pembelajaran Resitasi dan metode kerja kelompok pada materi Operasi hitung perkalian dan pembagian  belum mencapai target yang diharapkan. Hal ini berdasarkan ketuntasan belajar siswa 38,7% masih belum mencapai target. Pada siklus II pembelajaran  melalui penerapan model pembelajaran Resitasi dan metode kerja kelompok mengalami peningkatan. Hal ini berdasarkan ketuntasan belajar siswa 90,3% yang berarti sudah mencapai target. Kata Kunci: kerja kelompok; operasi hitung bilangan; resitasi